2014
DOI: 10.1002/cbic.201402384
|View full text |Cite
|
Sign up to set email alerts
|

Uncovering a Glycosyltransferase Provides Insights into the Glycosylation Step during Macrolactin and Bacillaene Biosynthesis

Abstract: Macrolactins (MLNs) have unique structural patterns containing a 24-membered ring lactone and diverse bioactivities. The MLN skeleton is biosynthesized via a trans-acyl transferase (AT) type I polyketide synthase (PKS) pathway, but the tailoring steps are still unknown. Herein, we report the identification of a glycosyltransferase (GT) gene bmmGT1, which is located at different locus from the MLN gene cluster in the genome of marine-derived Bacillus marinus B-9987, and its functional characterization as an MLN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
40
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 19 publications
(40 citation statements)
references
References 40 publications
(36 reference statements)
0
40
0
Order By: Relevance
“…In our previous study, we identified and characterized the GT gene bmmGT1 , which is involved in glycosylation of both MLNs and BAEs (Qin et al ., ). Interestingly, bmmGT1 is not a unique GT gene in the MLN‐producing strains, but instead it is also present in some other Bacillus genomes.…”
Section: Resultsmentioning
confidence: 97%
See 4 more Smart Citations
“…In our previous study, we identified and characterized the GT gene bmmGT1 , which is involved in glycosylation of both MLNs and BAEs (Qin et al ., ). Interestingly, bmmGT1 is not a unique GT gene in the MLN‐producing strains, but instead it is also present in some other Bacillus genomes.…”
Section: Resultsmentioning
confidence: 97%
“…, panel ii and iii). The above results indicated that bmmGT2 and bmmGT3 are not essential for the biosynthesis of glycosylated MLNs or BAEs, consistent with our previous result that bmmGT1 is responsible for the glycosylation steps of MLNs and BAEs in vivo (Qin et al ., ). In addition, the fermentation broth of ΔbmmGT1 mutant was further carefully checked by HPLC‐MS, in which we observed trace amount of glycosylated MLN ( 1b ) and BAE ( 4b ) (Supporting Information Fig.…”
Section: Resultsmentioning
confidence: 97%
See 3 more Smart Citations